Agri-entrepreneurial training needs of tribal youth in Odisha state, India - DASH, D; AMARDEEP, AMARDEEP; KAMESWARI, V L V; BHARDWAJ, N (The Indian Journal of Agricultural Sciences, 2021)
Tribal youth form a considerable part of the country’s tribal population. They face risks related to education,employment, training, drug and alcohol addiction, illiteracy, malnutrition, powerlessness, etc. Making tribal youthemployable is quite challenging and the government is putting efforts towards conducting skill-based training butstill, there is a lack of proper strategy. Agri-enterprises in tribal areas will be able to channelize tribal youth in aneffective manner for regional and consequently national development. Descriptive and analytical research designwas used to meet the objectives of the study. Twelve villages from 3 blocks of Koraput district of Odisha in the year2019–20 were selected purposively. A sample of 246 tribal youth was selected through proportional allocation byusing Cochran’s formula. Cronbach’s alpha was used to test the reliability of the sub areas under each major area ofagricultural enterprise and was found to be high (a–0.91). Training needs of tribal youth in various agri-enterpriseswere calculated through the Borich model of Training Need Assessment. It was found that the village was the mostfavourable place for receiving training for about 7–15 days in a group of 21–30 members in the evening hours fromOctober to December. Scientists and grass-root extension workers were preferred the most for conducting regularized agricultural trainings along with periodic follow-up visits by trainers for monitoring their progress. This research will assist the trainers in designing location-specific training module and help the policy makers to design suitable policies for tribal youth who aspire to take agricultural enterprises.